Konflik Sosial dalam Novel Tiba Sebelum Berangkat Karya Faisal Oddang - Ulfa Sazari; Yenni Hayati (Jurnal Bahasa dan Sastra, 2020)
This study aims to describe (1) the forms of social conflict in the Tiba Sebelum Berangkat’s novel by Faisal Oddang; (2) the causes of social conflict in the Tiba Sebelum Berangkat’s novel by Faisal Oddang; (3) the impact of social conflict in the Tiba Sebelum Berangkat’s novel by Faisal Oddang.This type of research is qualitative research using descriptive methods. The data contained in this study are in the form of words, phrases, clauses, and sentences that refer to social conflicts that occur in the Tiba Sebelum Berangkat’s novel by Faisal Oddang. The data source of this research is the Tiba Sebelum Berangkat’s novel by Faisal Oddang. The research instrument was the researcher himself with a tool in the form of a recording sheet to record matters relating to social conflicts contained in the Tiba Sebelum Berangkat’s novel by Faisal Oddang. Data collection techniques were carried out in several stages, namely (1) reading and understanding the novel that was the object of research; (2) marking the speeches of the characters and narrators in the novel in accordance with the data sought; (3) identifying data related to the research problem; (4) inventory data. The data validation technique used in this research is the triangulation technique. Data analysis technique is done by classifying data, interpreting data, and concluding research results.The results of the study found, namely: (1) the form of social conflict in the novel in the form of social conflict at the individual level, social conflict at the group or family level, and social conflict at the community level; (2) the causes of social conflict in the novel in the form of differences of opinion, differences in interests, and cultural conflicts; (3) the impact of social conflict in the novel in the form of inner destruction, loss of trust, and rift relations between individuals and groups.